Mali : Ex Post Assessment of Longer-Term Program Engagement; Staff Report; Statement by the Executive Director for Mali; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2011)
Ex Post Assessments are intended to provide an opportunity to step back from continuing program relations to consider an analysis of the economic problems facing the country, review progress under IMF-supported programs, and draw forward-looking lessons for future IMF engagement. The program objective of macroeconomic and financial stability was broadly achieved, as evidenced by the moderate fiscal deficits, low and relatively stable rates of inflation, and the maintenance of a sustainable external debt position; but raising economic growth remained a challenge. Structural reforms are also necessary to encourage investment and employment.